Modeling and numerical simulation of simultaneous heat and mass transfer during convective drying of porous materials. Issue 5 (March 2017) - Kahveci, Kamil
In this study, a model was developed and numerical simulations based on the developed model were performed to investigate the convective air drying behavior of porous materials and to discuss the reliability of assumptions often used in convective drying models. Simulation results were obtained for a wool yarn drying process with various values of the drying air temperature and inlet velocity. The results show that a symmetric pair of vortices is formed in the wake region of the material as a result of boundary separation. The length of the vortex formation increases with the inlet velocity, depending on the increase in the Reynolds number. The results also show that temperature is the major factor affecting the drying rate, while the velocity has a secondary effect. The results also show that the temperature in the material and on the surface of the material varies significantly depending on the evaporation rate, developing boundary layer, and boundary layer separation. Therefore, a constant temperature assumption in the material and on the material surface is not reasonable. Furthermore, the results show that the temperature gets significantly lower values, especially in the early stages of drying, due to the energy consumed for evaporation. Therefore, it is not reasonable to neglect evaporation, as this would result in an over-prediction of the drying rate.